EFEKTIFITAS METODE LANGSUNG TERHADAP MAHARAH KALAM PADA PROGRAM MUHADATSAH PONDOK PESANTREN MAMBA’US SHOLIHIN - Farid Qomaruddin; Muhammad A'inul Haq; Muh sabilar rosyad (MIYAH : Jurnal Studi Islam, 2023)
This study aims to determine the effectiveness of the direct method for Maharah Kalam in the Muhadatsah program at the Mamba'us Sholihin Suci Islamic boarding school, Manyar Gresik. This research is a Classroom Action Research which consists of 2 cycles with subjects being Arabic language education students in the second semester of the Mamba'us Sholihin Gresik Islamic boarding school. Data collection is done through tests, observations, and documentation. The results showed that the use of the direct method in the muhadatsah program was able to make learning effective. Student learning outcomes in cycle II experienced a significant increase based on the average student score, where at the beginning of the cycle there were 5 students with good grades, or around 26% increasing to 13 students or around 68%, and from none of the students with very good grades, it increased to 6 students or around 32% who had very good grades.